Mengukur Tingkat Usability pada Sistem Informasi Akademik (Studi Kasus: Akademik Universitas XYZ) - Thomas Alva Edison; Muhammad Affandes (UIN Sultan Syarif Kasim Riau, 2015)
Academic information system becomes a very important tool, because it is accessible by many users. The whole admin, lecturers and students use the system to conduct lectures. although the system is working well, there are still some issues that indicate the user to the menu that is not suitable, the form that has the wrong label, not working and any other problems, with many problems complained by the users, it is necessary to perform the measurement of the usability level of the system. the measurement is performed using jacob nielsen methode which using standards of 5 attributes: learnability, efficiency, memorability, errors, and satisfaction, based on interview with admins, lectures and students by doing direct observation to the system. the results of the research, there are 303 problems which affecting usability level of academic system, which amongst them are : 160 of admin section, 119 of lecturers section and 24 of students sections. based on those problems it is recommended to make a simplification of related form, align the name of the form, simplifying the menu, deleting the form, and provide the necessary information.Keywords: academic information system, jacob nielsen ,usability.